Towards a new web of rules: An international review of institutional experimentation to strengthen employment protections. Issue 2 (17th December 2018) - Wright, Chris F.; Wood, Alex J.; Trevor, Jonathan; McLaughlin, Colm; Huang, Wei; Harney, Brian; Geelan, Torsten; Colfer, Barry; Chang, Cheng; Brown, William
Abstract : Purpose: The purpose of this paper is to review "institutional experimentation" for protecting workers in response to the contraction of the standard employment relationship and the corresponding rise of "non-standard" forms of paid work. Design/methodology/approach: The paper draws on the existing research and knowledge base of the authors as well as a thorough review of the extant literature relating to: non-standard employment contracts; sources of labour supply engaging in non-standard work; exogenous pressures on the employment relationship; intermediaries that separate the management from the control of labour; and entities that subvert the employment relationship. Findings: Post-war industrial relations scholars characterised the traditional regulatory model of collective bargaining and the standard employment contract as a "web of rules". As work relations have become more market mediated, new institutional arrangements have developed to govern these relations and regulate the terms of engagement. The paper argues that these are indicative of an emergent "patchwork of rules" which are instructive for scholars, policymakers, workers' representatives and employers seeking solutions to the contraction of the traditional regulatory model. Research limitations/implications: While the review of the institutional experimentation is potentially instructive for developing solutions to gaps in labour regulation, a drawback of this approach is that there are limits to the realisation of policy transfer. Some of the initiatives discussed in the paper may be more effective than others for protecting workers on non-standard contracts, but further research is necessary to test their effectiveness including in different contexts. Social implications: The findings indicate that a task ahead for the representatives of government, labour and business is to determine how to adapt the emergent patchwork of rules to protect workers from the new vulnerabilities created by, for example, employer extraction and exploitation of their individual bio data, social media data and, not far off, their personal genome sequence. Originality/value: The paper addresses calls to examine the "institutional intersections" that have informed the changing ways that work is conducted and regulated. These intersections transcend international, national, sectoral and local units of analysis, as well as supply chains, fissured organisational dynamics, intermediaries and online platforms. The analysis also encompasses the broad range of stakeholders including businesses, labour and community groups, nongovernmental organisations and online communities that have influenced changing institutional approaches to employment protection.